International Partnership in Russia Conclusions from the Oil and Gas Industry - Henderson, James. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
International Partnership in Russia provides a unique insight into the joint ventures formed by international oil companies in Russia during the post-Soviet era. It outlines the highs and lows in their fortunes and analyses the reasons for their successes and failures.